Managing the impact of grassland management on nitrous oxide emissions through an improved understanding of soil microbial communities - Swaine, Mark (2018)
Nitrous oxide (N2O) plays an important role in the atmospheric radiative balance and in stratospheric ozone chemistry and has a global warming potential 298 times higher than CO2. Grasslands occupy two thirds of the agricultural land in the UK. have been estimated to emit up to 0.54 – 0.58 Gg of N2O per year. N2O is produced as a result of nitrifying and denitrifying soil microbial communties. Both microbial groups are strongly influenced by soil physical factors such as oxygen availability, with decreases in soil oxygen increasing N2O production from the soil. Grasslands are subject to a range of managment treatments that enhance the production of N2O, such as cattle traffic and the movement of heavy agricultural machinery, which increases soil bulk density, resulting in a reduction in available air-filled pore space. This in combination with the use of fertilisers, such as urea and cattle slurry and also the deposition of urine, lead to the ideal conditions for N2O production to proceed. Mitigation techniques, such as the use of nitrification inhibitors, such as Dicyandiamide (DCD) are used to reduce these emissions, however, even with the use of these nitrification inhibitors N2O emissions still proceed. An improved understanding of the effect of bulk density and soil water-filled pore space (WFPS), as well as the movement of gas through compacted soils is elucidated. The importance of soil heterotrophic nitrification was observed in compacted grassland soils and a crucial pathway of the effect of a commonly used eukaryotic protein synthesis inhibitor (cylcoheximide) used to distinguish between soil bacterial and fungal activity was highlighted and the implication for its use in soil nitrogen cycling studies is discussed. Limitations of DCD were also highlighted, with indications of alternative pathways of microbial N2O production in grassland soils treated with this nitrification inhibitor.